Crisis, Resilience, and the Time of Law. Issue 2 (August 2019) - Ellis, Jaye
Abstract: The important and no longer novel insight from ecology that ecosystems are dynamic and ever-changing along immensely complex causal pathways prompts the further insight that environmental protection regimes should promote not a particular ecosystemic end state, but rather ecosystem resilience, or the capacity to absorb and adapt to stress without compromising essential function. For law to embrace resilience as an objective, it is argued, it must itself be dynamic and flexible, capable of learning and adaptation. This poses potentially serious challenges to law's resilience: to what extent are flexibility and adaptability at odds with what Niklas Luhmann argues is an essential feature of normative systems, namely, resistance to learning in the face of disappointment? The potentially rapid rate of change expected of a law oriented to ecosystem resilience could overwhelm law's capacity to provide the measure of order, stability, and predictability that are core to its contribution, or prestation, to society. This paper takes this challenge seriously, but also explores another possible implication of law in the pursuit of ecosystem resilience: if environmental law is no longer conceived of in primarily instrumental terms, as a means to bring about a specific set of ecosystem objectives, there may be some possibility for its own resilience to be enhanced.